PENGGUNAAN MODEL âGROUP TO GROUP EXCHANGEâ UNTUK MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATA PELAJARAN TIK - Zakaria, - (WAHANA PEDAGOGIKA, 2016)
The analyzes showed that the national education today is faced with various crises that need immediate treatment, including issues related to the relevance or appropriateness between education and the needs of society and development. as a follow-up education policy in the context of regional autonomy and education units. Thus, through the SBCs government hopes the increasingly gaping gap between education and development, as well as the needs of the workforce can be resolved. Undertake this work from July to August 2013 in two cycles, each cycle consists of four stages: planning, implementation, observation and reflection. This study aims to meningktkan learning achievement using cooperative model GTGE techniques. The result of evaluation carried out for two cycles shows that in first cycle student s achievement are 74.70 and the second cycle are 80.89.